Inferring social context from observing the behaviour of others - Teoh, Yvonne Kah Hooi (2017)
Past research tells us that individuals can infer information about a target’s emotional state and intentions from their facial expressions (Frith & Frith, 2012), a process known as mentalising. More recently, it has been found that this ability extends to inferring the events that caused the facial reaction (e.g. Pillai, Sheppard, & Mitchell, 2012; Pillai et al., 2014), an ability known as retrodictive mindreading. In the current thesis, we enter a new territory where a series of experiments was conducted to investigate whether people (perceivers) can guess a target’s social context by observing their response to emotional stimuli. The core findings were: 1) perceivers were able to discriminate whether the targets were alone or observed by another person, 2) without any knowledge of the social context or what the targets were watching, perceivers judged whether targets were hiding or exaggerating their facial expressions, and their judgments discriminated between conditions in which targets were observed and alone, and 3) perceivers’ eye movements also systematically discriminated between conditions in which targets were observed and alone. Perceivers were thus able to infer – explicitly or implicitly - a target’s social context by observing their emotional response. Therefore, the findings demonstrate that people have the ability to use other people’s minds as a window onto a social context that could not be seen directly.